Negative pole piece, electrochemical device and electronic device
By using copolymers, including propylene monomers, in the bonding layer of the negative electrode sheet, the problem of insufficient cycling performance of the electrochemical device is solved, and the interface stability and energy density are improved.
Patent Information
- Application Number
- CN202411909285.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-09
- Publication Date
- 2025-03-28
AI Technical Summary
The cycling performance of existing electrochemical devices is insufficient, especially in terms of interface stability and bonding performance of the negative electrode sheet, resulting in poor energy density and rate performance.
An adhesive layer is provided between the negative electrode current collector and the negative electrode active material layer, and a copolymer is used in the adhesive layer. The monomer forming the copolymer includes at least a propylene monomer to improve the bonding performance and interface stability of the negative electrode sheet.
By improving the bonding layer performance of the negative electrode sheet, the interface stability of the electrochemical device during the circulation process is enhanced, and the circulation performance and energy density of the electrochemical device are improved.
Smart Images

Figure BDA0005205211270000091 
Figure BDA0005205211270000101 
Figure BDA0005205211270000131
Abstract
Description
[0001] This application is a divisional application of the invention patent with application number 202180002810.9 (International application number: PCT / CN2021 / 079812) filed on March 9, 2021, and the invention name is "Negative electrode sheet, electrochemical device and electronic device". Technical Field
[0002] The present application relates to the field of electrochemical energy storage, and in particular to negative electrode sheets, electrochemical devices and electronic devices. Background Art
[0003] With the development and progress of electrochemical devices (eg, lithium-ion batteries), higher and higher requirements are placed on their cycle performance. Although the current technology for improving electrochemical devices can improve the cycle performance of electrochemical devices to a certain extent, it is not satisfactory and further improvement is expected. Summary of the invention
[0004] An embodiment of the present application provides a negative electrode plate, which includes: a negative electrode collector; a bonding layer, including a copolymer, the monomers forming the copolymer include at least propylene monomers; and a negative electrode active material layer, wherein the bonding layer is arranged between the negative electrode collector and the negative electrode active material layer.
[0005] In some embodiments, the negative electrode sheet satisfies the following relationship (1), 0.1≤X / K≤0.75(1), wherein the unit area weight of the adhesive layer on the negative electrode current collector is X10 -4 mg / mm 2 , the bonding force between the negative electrode current collector and the bonding layer is KN / m. In some embodiments, 1≤X≤30, preferably, 1≤X≤10. In some embodiments, 1≤K≤100.
[0006] In some embodiments, the negative electrode sheet satisfies the following relationship (2): 3≤X / C≤350(2), wherein the unit area weight of the adhesive layer on the negative electrode current collector is X10 -4 mg / mm 2 , the unit area capacity of the negative electrode active material layer is C mAh / mm 2 In some embodiments, 3≤X / C≤100.
[0007] In some embodiments, the negative electrode sheet satisfies the following relationship (3), 0.2≤K / (R1-R2)≤100(3), wherein the bonding force between the negative electrode current collector and the bonding layer is KN / m, and the total resistance of the bonding layer and the negative electrode current collector is R1 mΩ·mm 2 , the resistance of the negative electrode current collector is R2 mΩ·mm 2 .
[0008] In some embodiments, propylene monomer accounts for 30mol% to 95mol% of the total monomer amount of the copolymer. In some embodiments, the copolymer is a particle, and the average particle size of the particle is 50μm or less. In some embodiments, the softening point of the copolymer is 70°C to 90°C. In some embodiments, the isotacticity of the copolymer is 35% to 80%. In some embodiments, the weight-average molecular weight of the copolymer is 500 to 1000000. In some embodiments, the swelling degree of the copolymer in diethyl carbonate is 40% or less. In some embodiments, the copolymer contains a polar functional group, and the polar functional group includes at least one of a hydroxyl group, an amino group, a carboxyl group or an ester group. In some embodiments, the monomers forming the copolymer also include at least one of ethylene, vinylidene fluoride, vinyl chloride, butadiene, isoprene, styrene, acrylonitrile, ethylene oxide, propylene oxide, acrylate, vinyl acetate or caprolactone.
[0009] In some embodiments, the negative electrode active material layer includes a silicon-based material, and the weight of the silicon-based material accounts for Y% of the total weight of the negative electrode active material layer, and 5≤Y≤95. In some embodiments, the bonding layer further includes a conductive agent, and the conductive agent includes at least one of carbon black, Ketjen black, graphene, carbon nanotubes, or carbon fibers.
[0010] Another embodiment of the present application provides an electrochemical device, comprising: a positive electrode sheet; a negative electrode sheet; and a separator, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet. The negative electrode sheet is any of the negative electrode sheets described above. In some embodiments, the electrochemical device further comprises an electrolyte, wherein the electrolyte comprises at least one of the following compounds:
[0011] (a) Propionate esters;
[0012] (b) organic compounds having a cyano group;
[0013] (c) lithium difluorophosphate;
[0014] (d)
[0015] in:
[0016] W is selected from
[0017] L is selected from a single bond or a methylene group;
[0018] m is an integer from 1 to 4;
[0019] n is an integer from 0 to 2; and
[0020] p is an integer from 0 to 6.
[0021] An embodiment of the present application further provides an electronic device, comprising the above-mentioned electrochemical device.
[0022] The embodiments of the present application improve the bonding between the negative electrode current collector and the negative electrode active material layer, enhance the interface stability of the corresponding electrochemical device during the cycle process, and improve the cycle performance of the electrochemical device by providing a bonding layer between the negative electrode current collector and the negative electrode active material layer, and the bonding layer includes a copolymer, and the monomers forming the copolymer include at least propylene monomers. DETAILED DESCRIPTION
[0023] The following embodiments may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way.
[0024] In some embodiments, the present application provides a negative electrode sheet, which may include a negative electrode current collector, a bonding layer and a negative electrode active material layer, wherein the bonding layer is located between the negative electrode current collector and the negative electrode active material layer. The negative electrode active material layer and the bonding layer may be disposed on one side or both sides of the negative electrode current collector.
[0025] In some embodiments, the bonding layer includes a copolymer, and the monomers forming the copolymer include at least propylene monomers. By providing a bonding layer between the negative electrode current collector and the negative electrode active material layer, and the bonding layer includes a copolymer, and the monomers forming the copolymer include at least propylene monomers, the bonding between the negative electrode current collector and the negative electrode active material layer is improved, the interface stability of the electrochemical device formed by the negative electrode plate during the cycle process is enhanced, and the cycle performance of the electrochemical device is improved.
[0026] In some embodiments, the negative electrode plate satisfies the following relationship (1):
[0027] 0.1≤X / K≤0.75 (1)
[0028] Among them, the unit area weight of the bonding layer on the negative electrode current collector is X10 -4 mg / mm 2 , the bonding force between the negative electrode current collector and the bonding layer is KN / m. X / K reflects the strength of the bonding performance of the bonding layer. When X / K is less than 0.1, it indicates that the bonding performance of the bonding layer is very strong. As the negative electrode active material layer expands and contracts during the cycle, it is easy to cause the negative electrode current collector to break, etc., because such a bonding layer lacks ductility. When X / K is greater than 0.75, it indicates that the bonding performance of the bonding layer is weak, and it is necessary to increase the coating area of the bonding layer or increase the coating amount to increase the bonding strength between the negative electrode current collector and the bonding layer, which will adversely affect the energy density of the electrochemical device. In some embodiments, 0.165≤X / K≤0.75. In some embodiments, 0.5≤X / K≤0.75. In this way, while ensuring the appropriate bonding force between the bonding layer and the negative electrode current collector, X is not too large, thereby minimizing the adverse effect on the energy density of the electrochemical device.
[0029] In some embodiments, 1≤X≤30. If X is less than 1, it may be detrimental to the bonding performance of the bonding layer due to the small weight of the bonding layer per unit area. If X is greater than 30, it will adversely affect the energy density of the electrochemical device. In some embodiments, 1≤X≤10. In this way, the adverse effect on the energy density of the electrochemical device can be minimized while ensuring the bonding performance of the bonding layer. In some embodiments, 1≤K≤100. If K is too small, it is not conducive to the bonding between the negative electrode current collector and the bonding layer; if K is too large, X is generally required to be larger, thereby adversely affecting the energy density of the electrochemical device.
[0030] In some embodiments, the negative electrode plate satisfies the following relationship (2):
[0031] 3≤X / C≤350 (2)
[0032] Among them, the unit area weight of the bonding layer on the negative electrode current collector is X10 -4 mg / mm 2 , the unit area capacity of the negative electrode active material layer is C mAh / mm 2 . The higher the unit area capacity (C) of the negative electrode active material layer, generally, the greater the coating amount of the negative electrode active material, and the larger the volume change caused by the insertion and extraction of lithium ions. Therefore, the unit area weight (X) of the bonding layer is correspondingly increased to increase the bonding force between the bonding layer and the negative electrode current collector. If X / C is less than 3, the bonding force between the bonding layer and the negative electrode current collector may be low, which may cause delamination. If X / C is greater than 350, it indicates that the unit area weight of the bonding layer may be too large, which adversely affects the energy density of the electrochemical device. In some embodiments, 3≤X / C≤100. By satisfying 3≤X / C≤100, while ensuring good bonding between the bonding layer and the negative electrode current collector, the adverse effect on the energy density of the electrochemical device is minimized.
[0033] In some embodiments, the negative electrode plate satisfies the following relationship (3):
[0034] 0.2≤K / (R1-R2)≤100 (3)
[0035] Among them, the bonding force between the negative electrode current collector and the bonding layer is KN / m, and the total resistance of the bonding layer and the negative electrode current collector is R1 mΩ·mm 2 , the resistance of the negative electrode current collector is R2 mΩ·mm 2. R1-R2 corresponds to the resistance of the bonding layer. If K / (R1-R2) is too small, for example, less than 0.2, it indicates that the bonding performance of the bonding layer is weak and the impedance is large. On the one hand, the weak bonding performance is not conducive to the bonding between the bonding layer and the negative electrode current collector. On the other hand, the large impedance is not conducive to the improvement of the rate performance of the electrochemical device. If K / (R1-R2) is too large, for example, greater than 100, it is necessary to increase the bonding force between the bonding layer and the negative electrode current collector and reduce the resistance of the bonding layer. Generally, increasing the bonding force between the bonding layer and the negative electrode current collector requires increasing the content of the viscous material in the bonding layer, and reducing the resistance of the bonding layer requires increasing the content of the conductive agent in the bonding layer. There is a certain balance between these two parameters, and it is difficult to achieve 100<K / (R1-R2).
[0036] In some embodiments, propylene monomer accounts for 30 mol% to 95 mol% of the total monomer amount of the copolymer. If the molar content of propylene monomer is too small, for example, less than 30%, it is not conducive to the excellent viscosity performance of the copolymer. In some embodiments, the copolymer is a particle, and the average particle size of the particle is 50 μm or less. If the average particle size of the copolymer particles is too large, for example, greater than 50 μm, on the one hand, it adversely affects the conductivity of the bonding layer, and on the other hand, it causes the specific surface area of the copolymer particles to be too small, which is not conducive to the full play of the bonding effect of the copolymer in the bonding layer. In some embodiments, the softening point of the copolymer is 70°C to 90°C. If the softening point of the copolymer is too low, for example, below 70°C, the structural stability of the copolymer is weak and it is easy to soften; if the softening point of the copolymer is too high, for example, greater than 90°C, it is not convenient for the processing of the bonding layer, and the processing cost of the bonding layer is increased.
[0037] In some embodiments, the isotacticity of the copolymer is 35% to 80%. The higher the isotacticity of the copolymer, the higher the crystallinity of the copolymer, and the better the melting point, tensile strength, bending modulus, impact strength and other properties. Therefore, if the isotacticity of the copolymer is too small, for example, less than 35%, the tensile strength and other properties of the copolymer are weak. However, if the isotacticity of the copolymer is too large, for example, greater than 80%, the tensile strength and other properties of the copolymer are too strong, and the ductility is insufficient, so that the negative electrode current collector is prone to breakage during the cycle.
[0038] In some embodiments, the weight average molecular weight of the copolymer is 500 to 1,000,000. If the weight average molecular weight of the copolymer is too low, the properties such as tensile strength of the copolymer are weak; if the weight average molecular weight of the copolymer is too large, it is not conducive to the processing of the copolymer. In some embodiments, the degree of swelling of the copolymer in diethyl carbonate is less than 40%. If the swelling degree of the copolymer in diethyl carbonate is too large, the volume expansion of the copolymer is large during the cycle of the electrochemical device, which is not conducive to the structural stability of the bonding layer and is prone to the risk of demolding.
[0039] In some embodiments, the copolymer comprises polar functional groups, and the polar functional groups include at least one of hydroxyl, amino, carboxyl or ester groups. By including these polar functional groups, the copolymer can better interact with other materials in the bonding layer or the negative electrode current collector, thereby enhancing the bonding properties of the bonding layer. In some embodiments, the monomers forming the copolymer also include at least one of ethylene, vinylidene fluoride, vinyl chloride, butadiene, isoprene, styrene, acrylonitrile, ethylene oxide, propylene oxide, acrylate, vinyl acetate or caprolactone.
[0040] In some embodiments, the bonding layer further includes a conductive agent, the conductive agent including at least one of carbon black, Ketjen black, graphene, carbon nanotubes or carbon fibers. By including a conductive agent in the bonding layer, the conductive properties of the bonding layer can be improved, thereby improving the DC impedance of the electrochemical device. In some embodiments, the weight content of the conductive agent in the bonding layer is 50% to 95%. In some embodiments, the thickness of the bonding layer can be 1 μm to 50 μm, but this is only exemplary and any other suitable thickness can be used.
[0041] In some embodiments, the negative electrode active material layer includes a silicon-based material, and the weight of the silicon-based material accounts for a percentage of Y% of the total weight of the negative electrode active material layer, and 5≤Y≤95. If the weight percentage of the silicon-based material in the negative electrode active material layer is too small, for example, less than 5%, the effect of using the silicon-based material to improve the energy density of the electrochemical device is limited. On the other hand, if the mass percentage of the silicon-based material in the negative electrode active material layer is too large, for example, greater than 95%, the negative electrode active material layer may cause a large volume expansion due to the high content of the silicon-based material, which is not conducive to the stability of the negative electrode solid electrolyte interface (SEI) film and may cause excessive consumption of the electrolyte. In some embodiments, the silicon-based material may include Si, SiO x , SiO2, SiC, Li2SiO5, Li2SiO3, Li4SiO4, at least one of silicon alloys, 0.6≤x≤1.5. In some embodiments, 0.1≤W / Y≤50, where W represents the resistance of the negative electrode active material layer (in mΩ·mm 2), the weight of the silicon-based material accounts for Y% of the total weight of the negative electrode active material layer. When W / Y is less than 0.1, it indicates that the weight content of the silicon-based material in the negative electrode active material layer may be too large, which may cause a large volume expansion during the cycle of the electrochemical device and cause the peeling of the negative electrode active material layer. W / Y is greater than 50, indicating that the resistance of the negative electrode active material layer is large, while the weight content of the silicon-based material is small. The large resistance of the negative electrode active material layer is not conducive to the improvement of the rate performance of the electrochemical device, while the small weight content of the silicon-based material is not conducive to the improvement of the energy density of the electrochemical device. In some embodiments, the silicon-based material includes silicon and oxygen, and the oxygen content in the silicon-based material is in the range of 3 atomic % to 40 atomic %. When within the above range, the capacity of the electrochemical device is high and can maintain good stability in the charge and discharge cycle.
[0042] In some embodiments, the negative electrode active material layer may further include a conductive agent and a binder, and the mass percentage of the binder in the negative electrode active material layer may be 0.5% to 10%. The mass percentage of the conductive agent in the negative electrode active material layer may be 0.5% to 10%. In some embodiments, the binder in the negative electrode active material layer may include at least one of carboxymethyl cellulose, polyacrylic acid, polyvinyl pyrrolidone, polyaniline, polyimide, polyamide-imide, polysiloxane, polystyrene-butadiene rubber, epoxy resin, polyester resin, polyurethane resin or polyfluorene. In some embodiments, the conductive agent in the negative electrode active material layer may include at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon fibers, conductive carbon black, acetylene black, Ketjen black, conductive graphite or graphene. It should be understood that the material types and mass percentages of the conductive agent and binder in the negative electrode active material layer are only exemplary, and other suitable materials and mass percentages may also be used.
[0043] In some embodiments, the negative electrode current collector of the negative electrode plate can be at least one of copper foil, nickel foil or carbon-based current collector. In some embodiments, the compaction density of the negative active material layer of the negative electrode plate can be 1.0 g / cm 3 Up to 2.2g / cm 3 If the compaction density of the negative electrode active material layer is too small, the volume energy density of the electrochemical device is lost. If the compaction density of the negative electrode active material layer is too large, it is not conducive to the passage of lithium ions, polarization increases, the electrochemical performance is affected, and lithium is easily precipitated during the charging process of the electrochemical device.
[0044] Some embodiments of the present application provide an electrochemical device, the electrochemical device comprising an electrode assembly, the electrode assembly comprising a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet is any of the negative electrode sheets described above.
[0045] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer is disposed on one or both sides of the positive current collector. In some embodiments, the positive current collector may be Al foil, and of course, other positive current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive current collector may be 1 μm to 50 μm. In some embodiments, the positive active material layer may be coated only on a partial area of the positive current collector. In some embodiments, the thickness of the positive active material layer may be 10 μm to 500 μm. In some embodiments, the positive active material layer includes a positive active material. In some embodiments, the positive active material may include at least one of lithium cobaltate, lithium manganate, lithium iron phosphate, lithium iron manganese phosphate, lithium-rich manganese-based material, lithium nickel cobalt manganate, lithium nickel cobalt aluminum or lithium nickel manganate. In some embodiments, the positive active material layer also includes a binder and a conductive agent. In some embodiments, the binder in the positive electrode active material layer may include at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, a styrene-acrylate copolymer, a styrene-butadiene copolymer, a polyamide, a polyacrylonitrile, a polyacrylate, a polyacrylic acid, a polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, a polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. In some embodiments, the conductive agent in the positive electrode active material layer may include at least one of conductive carbon black, Ketjen black, lamellar graphite, graphene, carbon nanotubes or carbon fibers. In some embodiments, the mass ratio of the positive electrode active material, the conductive agent and the binder in the positive electrode active material layer may be (70 to 98): (1 to 15): (1 to 15). It should be understood that the above is only an example, and the positive electrode active material layer may adopt any other suitable material, thickness and mass ratio.
[0046] In some embodiments, the separator includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the stability of the battery through the shutdown effect. In some embodiments, the thickness of the separator is in the range of about 5 μm to 500 μm.
[0047] In some embodiments, the surface of the isolation membrane may further include a porous layer, the porous layer being disposed on at least one surface of the substrate of the isolation membrane, the porous layer comprising inorganic particles and a binder, the inorganic particles being selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. In some embodiments, the pores of the isolation membrane have a diameter in the range of about 0.01 μm to 1 μm. The binder of the porous layer is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the separator can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the separator, and enhance the adhesion between the separator and the pole piece.
[0048] In some embodiments of the present application, the electrode assembly of the electrochemical device is a wound electrode assembly, a folded electrode assembly, or a stacked electrode assembly.
[0049] In some embodiments, the electrochemical device includes a lithium ion battery, but the present application is not limited thereto. In some embodiments, the electrochemical device may further include an electrolyte. The electrolyte may be one or more of a gel electrolyte, a solid electrolyte, and an electrolyte, the electrolyte including a lithium salt and a non-aqueous solvent. The lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB or lithium difluoroborate. For example, the lithium salt is selected from LiPF6 because it can provide high ionic conductivity and improve cycle characteristics.
[0050] In some embodiments, the electrolyte includes at least one of the following compounds:
[0051] (a) Propionate esters;
[0052] (b) organic compounds having a cyano group;
[0053] (c) lithium difluorophosphate;
[0054] (d)
[0055] in:
[0056] W is selected from
[0057] L is selected from a single bond or a methylene group;
[0058] m is an integer from 1 to 4;
[0059] n is an integer from 0 to 2; and
[0060] p is an integer from 0 to 6.
[0061] Propionate / organic compounds with cyano groups can significantly improve the cycle performance of electrochemical devices; the addition of LiPO2F2 can enhance the lithium ion transport capacity of the electrolyte, thereby improving the DC impedance of the electrochemical device. As a result, the capacity retention rate and DC impedance (DCR) of the electrochemical device using the electrolyte containing the above compounds are significantly improved.
[0062] In some embodiments, the propionate ester is a compound represented by the following formula:
[0063]
[0064] in:
[0065] R 1 Selected from ethyl or halogenated ethyl,
[0066] R 2 Selected from C1-C6 alkyl or C1-C6 haloalkyl.
[0067] In some embodiments, propionate includes at least one of methyl propionate, ethyl propionate, propyl propionate, butyl propionate, pentyl propionate, methyl halopropionate, ethyl halopropionate, propyl halopropionate, butyl halopropionate or pentyl halopropionate. In some embodiments, the halogen group in methyl halopropionate, ethyl halopropionate, propyl halopropionate, butyl halopropionate and pentyl halopropionate includes at least one of fluorine group (-F), chlorine group (-Cl), bromine group (-Br) or iodine group (-I).
[0068] In some embodiments, the weight content of propionate is 10 wt % to 65 wt % based on the total weight of the electrolyte. In some embodiments, the weight content of propionate is 15 wt % to 60 wt % based on the total weight of the electrolyte. In some embodiments, the weight content of propionate is 30 wt % to 50 wt % based on the total weight of the electrolyte. In some embodiments, the weight content of propionate is 30 wt % to 40 wt % based on the total weight of the electrolyte.
[0069] In some embodiments, the compound having a cyano group includes succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane, 1,4-dicyanopentane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, ethylene glycol bis(propionitrile) ether, 3,5- Dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, diethylene glycol bis(2-cyanoethyl) ether, triethylene glycol bis(2-cyanoethyl) ether, tetraethylene glycol bis(2-cyanoethyl) ether, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol bis(4-cyanobutyl) ether, 1,4-dicyano-2-butene, 1,4-dicyano 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexatriconitrile, 1,2,6-hexatriconitrile, 1,2,3 -tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane or 1,2,5-tris(cyanoethoxy)pentane at least one. In some embodiments, based on the total weight of the electrolyte, the weight content of the compound having a cyano group is 0.1wt% to 15wt%. In some embodiments, based on the total weight of the electrolyte, the weight content of the compound having a cyano group is 0.5wt% to 10wt%. In some embodiments, based on the total weight of the electrolyte, the weight content of the compound having a cyano group is 1wt% to 8wt%. In some embodiments, based on the total weight of the electrolyte, the weight content of the compound having a cyano group is 3wt% to 5wt%.
[0070] In some embodiments, the weight content of lithium difluorophosphate is 0.01wt% to 15wt% based on the total weight of the electrolyte. In some embodiments, the weight content of lithium difluorophosphate is 0.05wt% to 12wt% based on the total weight of the electrolyte. In some embodiments, the weight content of lithium difluorophosphate is 0.1wt% to 10wt% based on the total weight of the electrolyte. In some embodiments, the weight content of lithium difluorophosphate is 0.5wt% to 8wt% based on the total weight of the electrolyte. In some embodiments, the weight content of lithium difluorophosphate is 1wt% to 5wt% based on the total weight of the electrolyte. In some embodiments, the weight content of lithium difluorophosphate is 2wt% to 4wt% based on the total weight of the electrolyte.
[0071] In some embodiments, the compound of Formula 1 includes at least one of the following compounds:
[0072]
[0073] wherein m is an integer from 1 to 4; n is an integer from 0 to 2; and p is an integer from 0 to 6.
[0074] In some embodiments of the present application, taking a lithium-ion battery as an example, a positive electrode sheet, a separator, and a negative electrode sheet are sequentially wound, folded, or stacked into an electrode assembly, and then encapsulated in, for example, an aluminum-plastic film, injected with an electrolyte, formed, and encapsulated to produce a lithium-ion battery. Then, the prepared lithium-ion battery is subjected to a performance test.
[0075] Those skilled in the art will appreciate that the above-described method for preparing an electrochemical device (eg, a lithium-ion battery) is only an example, and other methods commonly used in the art may be used without departing from the disclosure of the present application.
[0076] Embodiments of the present application also provide electronic devices including the above-mentioned electrochemical devices. The electronic devices of the embodiments of the present application are not particularly limited, and they can be any electronic devices known in the prior art. In some embodiments, the electronic device can include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0077] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.
[0078] Example 1
[0079] Preparation of positive electrode sheet: The positive electrode active material lithium cobalt oxide, conductive agent conductive carbon black, and binder polyvinylidene fluoride (PVDF) are dissolved in N-methylpyrrolidone (NMP) solution in a weight ratio of 95:2:3 to form positive electrode slurry. A 12μm aluminum foil is used as the positive electrode current collector, and the positive electrode slurry is coated on the positive electrode current collector with a coating amount of 18.37mg / cm 2 After drying, cold pressing and cutting, the positive electrode sheet is obtained.
[0080] Preparation of negative electrode sheet: Compound 1 and conductive carbon black were dissolved in deionized water at a weight ratio of 50:50 to form a bonding layer slurry. A 12 μm copper foil was used as the negative electrode current collector, and the bonding layer slurry was coated on the negative electrode current collector and dried to obtain a bonding layer. The unit area weight X of the bonding layer was 2×10 -4 mg / mm 2 .
[0081] Artificial graphite, silicon-based material SiO, conductive carbon black, polyacrylic acid (PAA) and sodium carboxymethyl cellulose were dissolved in deionized water in a weight ratio of 83.5:10:1:5:0.5 to form a negative electrode active material layer slurry. The negative electrode active material layer slurry was coated on the bonding layer with a coating amount of 9.3 mg / cm 2 , dried, and cut to obtain the negative electrode sheet.
[0082] Preparation of isolation membrane: The isolation membrane substrate is 9 μm thick polyethylene (PE), and a 2 μm alumina ceramic layer is coated on both sides of the isolation membrane substrate. Finally, 2.5 mg of binder polyvinylidene fluoride (PVDF) is coated on both sides of the ceramic layer and dried.
[0083] Preparation of electrolyte: In an environment with a water content of less than 10 ppm, add LiPF6 to a non-aqueous organic solvent (propylene carbonate (PC), ethylene carbonate (EC): diethyl carbonate (DEC) = 1:1:1, weight ratio), the concentration of LiPF6 is 1.15 mol / L, mix well, and obtain an electrolyte.
[0084] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package, and obtain the lithium-ion battery through the process of formation, degassing, trimming, etc.
[0085] The examples and comparative examples are based on the steps of Example 1 with parameter changes.
[0086] In Comparative Example 1, the negative electrode plate does not include a bonding layer, the negative electrode active material layer is directly coated on the negative electrode current collector, and other conditions are the same as those in Example 1.
[0087] In Examples 2 to 4 and Examples 9 to 10, the weight per unit area X of the binding layer on the negative electrode current collector is different from that in Example 1, and the binding force K between the negative electrode current collector and the binding layer is different from that in Example 1.
[0088] In Examples 5 to 8, the type of copolymer in the bonding layer and the unit area weight X of the bonding layer on the negative electrode current collector are different from those in Example 1, and the bonding force K between the negative electrode current collector and the bonding layer is different from that in Example 1. The copolymer used in Example 5 is Compound 2, the copolymer used in Example 6 is Compound 3, the copolymer used in Example 7 is Compound 4, and the copolymer used in Example 8 is Compound 5.
[0089] In Comparative Example 2, no copolymer is contained, and the unit area weight X of the binding layer on the negative electrode current collector is different from that of Example 1.
[0090] In Examples 11 to 17, the weight per unit area X of the binding layer on the negative electrode current collector and the capacity per unit area C of the negative electrode active material layer are different from those in Example 1.
[0091] In Examples 18 to 22, the bonding force K between the negative electrode current collector and the bonding layer and the resistance R1-R2 of the bonding layer are different from those in Example 1.
[0092] In Examples 23 to 27, the copolymers used, the bonding force K between the negative electrode current collector and the bonding layer, and the resistance R1-R2 of the bonding layer are different from those in Example 1. Example 23 uses Example 2, Example 24 uses Example 3, Example 25 uses Example 4, Example 26 uses Example 5, and Example 27 uses Example 5.
[0093] In Examples 28 to 55, compared to Example 1, additional additives were added to the electrolyte.
[0094] In addition, some parameters of the copolymer are shown in Table 1 below:
[0095] Table 1
[0096]
[0097] The test methods for various parameters of this application are described below.
[0098] Test method for cycle capacity retention rate:
[0099] At 45°C, the lithium-ion battery is charged to 4.45V at a constant current of 1C, then charged to a current of 0.05C at a constant voltage of 4.45V, and then discharged to 3.0V at a constant current of 1C. This is the first cycle. The lithium-ion battery is cycled 200 times under the above conditions. "1C" is the current value that completely discharges the battery capacity within 1 hour. The capacity retention rate of the lithium-ion battery after cycling is calculated by the following formula:
[0100] Cycle capacity retention rate = (discharge capacity after 200 cycles / discharge capacity at the first cycle) × 100%.
[0101] Thickness expansion rate test method:
[0102] At 45°C, the lithium-ion battery was charged to 4.45V at 1C constant current, then charged to 0.05C at 4.45V constant voltage, and the thickness of the lithium-ion battery was tested using a 500g flat plate thickness gauge (PPG), and then discharged to 3.0V at 1C constant current. This was the first cycle. The lithium-ion battery was cycled 200 times under the above conditions. The thickness expansion rate of the lithium-ion battery after cycling was calculated by the following formula:
[0103] Thickness expansion ratio = ((thickness of lithium-ion battery after 200 cycles - thickness of lithium-ion battery at the first cycle) / thickness of lithium-ion battery at the first cycle)) × 100%.
[0104] Test method for the bonding strength (KN / m) between the negative electrode current collector and the bonding layer:
[0105] At room temperature, the current collector coated with the adhesive layer is cut into strips with a width of 15 mm and a length of 20 cm. One side of the adhesive layer is glued to the test mold (long metal block) with a strong double-sided adhesive tape, and the current collector is pulled with a high-speed rail tensile machine at a constant tensile force (the tensile force direction is parallel to the test mold). After the tensile force stabilizes, the tensile force F value is recorded. The thickness expansion rate of lithium-ion batteries after cycling is calculated by the following formula:
[0106] Adhesion force K = tension after stabilization F / negative electrode current collector width L.
[0107] Test method for the resistance R1 of the bonding layer and the negative electrode current collector, and the resistance R2 of the negative electrode current collector:
[0108] At room temperature, cut the negative electrode current collector coated with the adhesive layer and the uncoated negative electrode current collector into square pieces of about 6cm*8cm. Place the sample on the test bench to ensure that the sample completely covers the circular hole of the mold (Yuan Neng Technology Diaphragm Resistance Tester). The air pressure is 0.7Mpa and the pressure is 0.4T. Record the test resistances R1 and R2 respectively.
[0109] DC resistance (DCR) test method:
[0110] At room temperature, adjust the lithium-ion battery to a specified state of charge (SOC) (50% SOC is used in this application), discharge it for a short time (1s is used in this application) at a specified current density I (1C is used in this experiment), and record the voltage V1 and V2 of the lithium-ion battery before and after discharge. The DCR can be calculated by the following formula.
[0111] DCR=(V1-V2) / I.
[0112] Table 2 shows various parameters and evaluation results of Examples 1 to 4, Examples 9 to 10, and Comparative Example 1.
[0113] Copolymer X K X / K Cycle capacity retention rate Thickness expansion rate Comparative Example 1 / / / / 72% 18.2% Example 1 Compound 1 2 12 0.167 81% 15.1% Example 2 Compound 1 2.3 15 0.153 84% 14.2% Example 3 Compound 1 2.8 15 0.187 82% 15.1% Example 4 Compound 1 4.7 42 0.112 87% 11.2% Example 9 Compound 1 21.2 12 1.77 53% 15.2% Example 10 Compound 1 2.4 31 0.077 47% 12.6%
[0114] Here, “ / ” means non-existence, the same below.
[0115] By comparing Examples 1 to 4 and Comparative Example 1, it can be seen that by using a bonding layer including a copolymer, wherein the copolymer includes propylene monomer, the cycle capacity retention rate and thickness expansion rate of the lithium ion battery are significantly improved.
[0116] In addition, by comparing Examples 1 to 4, it can be seen that when 0.1≤X / K≤0.75, as X / K increases, the cycle capacity retention rate of the lithium ion battery tends to decrease, while the thickness expansion rate of the lithium ion battery tends to increase. By comparing Examples 1 to 4 and Examples 9 to 10, it can be seen that when X / K is too small or too large, although the thickness expansion rate of the lithium ion battery is improved to a certain extent, the cycle capacity retention rate of the lithium ion battery will deteriorate to a certain extent.
[0117] Table 3 shows various parameters and evaluation results of Examples 5 to 8 and Comparative Example 1.
[0118] Table 3
[0119]
[0120]
[0121] By comparing Examples 5 to 8 and Comparative Example 1, it can be seen that by adopting a bonding layer including some other copolymers besides Compound 1, wherein the copolymer includes propylene monomer, the cycle capacity retention rate and thickness expansion rate of the lithium ion battery can also be significantly improved.
[0122] Table 4 shows various parameters and evaluation results of Examples 11 to 17 and Comparative Example 2.
[0123] Table 4
[0124] Copolymer X C X / C Cycle capacity retention rate DCR(mΩ) Comparative Example 2 / 10 0.031 352.58 82% 60.848 Embodiment 11 Compound 1 0.14 0.043 3.26 88% 38.116 Example 12 Compound 1 2.8 0.057 49.12 92% 39.666 Example 13 Compound 1 4.6 0.063 73.02 85% 41.459 Embodiment 14 Compound 1 4.7 0.064 73.44 82% 38.999 Embodiment 15 Compound 1 5.1 0.092 55.43 85% 38.552 Example 16 Compound 1 6.5 0.051 127.45 87% 46.666 Embodiment 17 Compound 1 9.6 0.031 309.68 83% 54.234
[0125] By comparing Examples 11 to 17 with Comparative Example 2, it can be seen that the use of a copolymer including propylene monomers in the adhesive layer improves the cycle capacity retention rate of the lithium ion battery to a certain extent, and the DC impedance of the lithium ion battery is significantly improved. In addition, when 3≤X / C≤350, as X / C increases, the cycle capacity retention rate of the lithium ion battery begins to increase, then decreases, then increases again, then decreases again, and the DC impedance of the lithium ion battery tends to increase.
[0126] Table 5 shows the respective parameters and evaluation results of Examples 18 to 27.
[0127] Table 5
[0128] Copolymer K <![CDATA[R1]]> <![CDATA[R2]]> <![CDATA[R1-R2]]> <![CDATA[K / (R1-R2)]]> Cycle capacity retention rate Thickness expansion rate Embodiment 18 Compound 1 20 15.2 1.3 13.9 1.44 77.8% 10.1% Embodiment 19 Compound 1 12 14.5 2.6 11.9 1.01 80.2% 19.3% Embodiment 20 Compound 1 15 29.2 4.7 24.5 0.61 81.0% 14.1% Embodiment 21 Compound 1 15 7.4 5.8 1.6 9.38 79.4% 9.8% Embodiment 22 Compound 1 30 11.7 7.2 4.5 6.67 80.2% 19.3% Embodiment 23 Compound 2 28 58.8 7.7 51.1 0.55 74.1% 10.1% Embodiment 24 Compound 3 32 15.3 14.1 1.2 26.67 90.4% 11.1% Embodiment 25 Compound 4 39 19.5 18.8 0.7 55.71 50.2% 15.9% Embodiment 26 Compound 5 34 42 30 12 2.83 81.5% 13.2% Embodiment 27 Compound 5 30 92.9 49.1 43.8 0.68 83% 10.9%
[0129] As shown in Table 4, as K / (R1-R2) increases, the capacity retention rate of the lithium-ion battery shows a trend of first decreasing and then increasing. As K / (R1-R2) increases, the thickness expansion rate of the electrochemical device shows a trend of first increasing and then decreasing.
[0130] Table 6 shows various parameters and evaluation results of Examples 28 to 55 and Example 1.
[0131] Table 6
[0132]
[0133] By comparing Examples 28 to 55 with Example 1, it can be seen that adding additives such as propionate, organic compounds with cyano groups and / or difluorophosphates to the electrolyte can significantly improve the cycle capacity retention rate and DC impedance of the electrochemical device. This is because propionate / organic compounds with cyano groups can improve the formation of the SEI film on the surface of the negative electrode; the addition of difluorophosphates can enhance the lithium ion transport capacity of the electrolyte and improve the internal resistance of the electrochemical device.
[0134] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features. For example, the above features are replaced with the technical features with similar functions disclosed in the present application.
Claims
1. An electrochemical device comprising: Negative electrode; Electrolyte; The negative electrode plate comprises: Anode current collector; A bonding layer comprising a copolymer, wherein the monomers forming the copolymer at least comprise propylene monomers; a negative electrode active material layer, wherein the bonding layer is disposed between the negative electrode current collector and the negative electrode active material layer; The electrolyte comprises at least one of the following compounds: (a) Propionate esters; (b) organic compounds having a cyano group; (c) lithium difluorophosphate; (d) in: W is selected from L is selected from a single bond or a methylene group; m is an integer from 1 to 4; n is an integer from 0 to 2; and p is an integer from 0 to 6.
2. The electrochemical device according to claim 1, wherein: The negative electrode plate satisfies the following relation (1): 0.1≤X / K≤0.75 (1) Wherein, the unit area weight of the bonding layer on the negative electrode current collector is X10 -4 mg / mm 2 , the bonding force between the negative electrode current collector and the bonding layer is KN / m.
3. The electrochemical device according to claim 2, wherein: 1≤X≤30, preferably, 1≤X≤10.
4. The electrochemical device according to claim 2, wherein: 1≤K≤100。 5. The electrochemical device according to claim 1, wherein The negative electrode plate satisfies the following relation (2): 3≤X / C≤350 (2) Wherein, the unit area weight of the bonding layer on the negative electrode current collector is X10 -4 mg / mm 2 The capacity per unit area of the negative electrode active material layer is C mAh / mm 2 .
6. The electrochemical device according to claim 5, wherein: 3≤X / C≤100.
7. The electrochemical device according to claim 1, wherein: The negative electrode plate satisfies the following relation (3): 0.2≤K / (R1-R2)≤100 (3) The bonding force between the negative electrode current collector and the bonding layer is KN / m, and the total resistance of the bonding layer and the negative electrode current collector is R1 mΩ·mm 2 The resistance of the negative electrode current collector is R2mΩ·mm 2 .
8. The electrochemical device according to claim 1, wherein The copolymer has at least one of the following characteristics: (a) the propylene monomer accounts for 30 mol% to 95 mol% of the total monomers forming the copolymer; (b) the copolymer is in the form of particles, and the average particle size of the particles is less than 50 μm; (c) the copolymer has a softening point of 70°C to 90°C; (d) the isotacticity of the copolymer is 35% to 80%; (e) the weight average molecular weight of the copolymer is 500 to 1,000,000; (f) The degree of swelling of the copolymer in diethyl carbonate is 40% or less.
9. The electrochemical device according to claim 1, wherein: The copolymer comprises a polar functional group, and the polar functional group includes at least one of a hydroxyl group, an amino group, a carboxyl group, or an ester group.
10. The electrochemical device according to claim 1, wherein The monomers forming the copolymer further include at least one of ethylene, vinylidene fluoride, vinyl chloride, butadiene, isoprene, styrene, acrylonitrile, ethylene oxide, propylene oxide, acrylate, vinyl acetate or caprolactone.
11. The electrochemical device according to claim 1, wherein The negative electrode active material layer includes a silicon-based material, and the weight of the silicon-based material accounts for Y% of the total weight of the negative electrode active material layer, and 5≤Y≤95.
12. The electrochemical device according to claim 1, wherein The bonding layer further includes a conductive agent, and the conductive agent includes at least one of carbon black, Ketjen black, graphene, carbon nanotubes or carbon fibers.
13. The electrochemical device according to claim 11, wherein The negative electrode plate satisfies the following relation (4): 0.1≤W / Y≤50 (4) The resistance of the negative electrode active material layer is W mΩ·mm 2 .
14. An electronic device comprising the electrochemical device according to claims 1 to 13.